Atuação do tradutor intérprete de libras na aprendizagem matemática de surdos no Ensino Fundamental - Ana Carolina Machado Ferrari (2014)
The main goal of this research was to investigate the boundaries, possibilities and implications of the work of the interpreter translator of LIBRAS in mathematics learning of Deaf in classrooms of elementary school. More precisely, we sought to understand how this performance approaches or moves away from mathematical knowledge taught by hearing teacher. The theoretical framework that supported the study involved the literature on the education of the Deaf throughout history, the inclusion of the Deaf in regular schools, the work of the interpreter and a sociocultural view of mathematics learning of the Deaf. The participants of the research was the Deaf students, mathematics teachers and interpreters of LIBRAS from three classes (two 7th and 8th grade and one from EJA) of elementary school in two schools of Municipal School of Belo Horizonte. The working strategy followed the usual lines of a qualitative research in education, using as instruments of data production, audio recording and video observations in classrooms and semi-structured interviews, and field diary journal. For data analysis two episodes occurred in groups of 7 and 8 years were selected. Excerpts from interviews with both the hearing teacher and the interpreter of LIBRAS of EJA were also discussed. In case of the 7th and 8th grades interpreters was checked that both studentes moved away from mathematical knowledge taught by the teacher for two main reasons: lack of specific training in mathematics or previous contacts with the mathematical content to be worked in the classroom, and lack of technical competence in LIBRAS. Regarding the class of EJA, we noticed a tension between the hearing teacher and the interpreter of LIBRAS about the responsibility of Deaf student learning. In all cases, there is an indication that only the interpreter of LIBRAS in the classroom is not sufficient for a meaningful mathematical learning for the Deaf. Further, direct interactions between hearing teacher and Deaf students are desirable. It was concluded that the limited scope of the interpreter in the classroom is obscure for the teachers, interpreters and Deaf students. Finally, some questions were raised about the training of teachers and interpreters of LIBRAS that could be useful for future research on the topic.